2002
DOI: 10.1159/000062991
|View full text |Cite
|
Sign up to set email alerts
|

Study of Psychopathology in Patients with Chronic Non-Lesional Epilepsy: A Minnesota Multiphasic Personality Inventory Profile Controlled Study

Abstract: Objective: Psychiatric morbidity and psychopathology have been widely assessed in patients with epilepsy. However, the issue of whether people with epilepsy are at increased risk for psychopathology remains highly controversial. These disorders are not evaluated in a systematic manner in patients with non-lesional epilepsy, so they could be underestimated. The objective is to evaluate personality disorders in patients with non-lesional epilepsy. Methods: In this study, we investigated the presence of personali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Dikmen et al 25 however, found that MMPI is sensitive to behavioural abnormalities in patients with different seizure categories. A study by Modrego et al 26 also supports the validity of MMPI for detection of abnormal behaviour in patients with chronic non-lesional epilepsy. Compared with the Diagnostic and Statistical Manual of Mental Disorders-Version Four (DSM-IV) criteria, the MMPI correctly identified personality disorders, especially depression and paranoid personality.…”
Section: Discussionmentioning
confidence: 77%
“…Dikmen et al 25 however, found that MMPI is sensitive to behavioural abnormalities in patients with different seizure categories. A study by Modrego et al 26 also supports the validity of MMPI for detection of abnormal behaviour in patients with chronic non-lesional epilepsy. Compared with the Diagnostic and Statistical Manual of Mental Disorders-Version Four (DSM-IV) criteria, the MMPI correctly identified personality disorders, especially depression and paranoid personality.…”
Section: Discussionmentioning
confidence: 77%
“…Among the “probably symptomatic” subjects, the positive relationship between AED resistance and psychiatric pathologies can be interpreted as a reactive condition in patients whose seizures are constraining in the absence of any significant neurologic or cognitive defects (Beghi et al., 2002; Modrego et al., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…5 Modergo et al noticed a high prevalence of schizophrenia traits (57%) compared to other personality changes in non-lesional epilepsy patients. 6 The schizophrenia traits, paranoid disorder and aggressive behavior lead to many psychosocial problems, such as social maladjustment, poor self-esteem, depressive feelings, reduced attention control, impaired cognitive function and difficulties in reversal learning, [7][8][9] which significantly compromise patients' quality of life.…”
Section: Introductionmentioning
confidence: 99%